2007
DOI: 10.1080/15419060701463082
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plakophilin-1 Expression Promotes Increased Motility in Head and Neck Squamous Cell Carcinoma Cells

Abstract: Desmosomes are prominent cell-cell adhesive junctions found in a variety of epithelial tissues, including the oral epithelium. The transmembrane core of the desmosome is composed of the desmosomal cadherins that interact extracellularly to mediate cell-cell adhesion. The cytoplasmic domain of desmosomal cadherins interact with plaque proteins that in turn interact with the keratin intermediate filament cytoskeleton. Plakophilin 1 is a major desmosomal plaque component that functions to recruit intermediate fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…In addition, we have previously shown parental UM-SCC-38 cells are relatively immobile in culture. 13 We retrovirally expressed human Slug in UM-SCC-38 cells to generate a population of UM-SCC-38 cells expressing Slug. UM-SCC-38/slug cells display a distinct change in morphology compared to UM-SCC-38/neo cells infected with virus conferring G418 resistance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have previously shown parental UM-SCC-38 cells are relatively immobile in culture. 13 We retrovirally expressed human Slug in UM-SCC-38 cells to generate a population of UM-SCC-38 cells expressing Slug. UM-SCC-38/slug cells display a distinct change in morphology compared to UM-SCC-38/neo cells infected with virus conferring G418 resistance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of these studies are contradictory with up-regulation, down-regulation, or maintenance of desmosome components being reported. While the expression of PKPs1 -3 was increased in certain cancers of various origin (Furukawa et al, 2005;Cheung et al, 2007;Demirag et al, 2012;Takahashi et al, 2012), the loss or reduction of PKPs1 -3 was observed in the development and/or progression of the same or other cancers (Sobolik-Delmaire et al, 2007;Narayana et al, 2010;Demirag et al, 2011;Takahashi et al, 2012). Both conditions were correlated with advanced tumor grade, increased metastasis and/or poor prognosis.…”
Section: Pkp Function In Cancer: Loss or Gain Of Function?mentioning
confidence: 98%
“…A431D and A431DE cells were described previously (Lewis et al, 1997;Wahl, 2005). Generation of retroviral particles and retroviral infection has been described previously (Roberts et al, 2011;Sobolik-Delmaire et al, 2007). Retrovirally infected cell populations were routinely grown in DMEM containing 500 mg/ml G418 (Mediatech, Herndon, VA).…”
Section: Cell Culturementioning
confidence: 99%
“…Antibodies against desmoplakin (20B6), desmoglein-2 (6D8), E-cadherin (4A2) and desmocollin-2/3 (7G6) were as described previously (Bazzi et al, 2006;Nieman et al, 1999;Sobolik-Delmaire et al, 2007;Wahl et al, 1996). Rabbit anti-desmoplakin (NW6) was a kind gift of Kathleen Green (Northwestern University, Chicago, IL).…”
Section: Antibodiesmentioning
confidence: 99%